Worldview aspects of the kazakh women’s national costume as a factor of the development of youth thinking culture - Aldanayeva, Tomiris; Mikhailova, Natalia (Pedagogy and Psychology, 2021)
In this article, the Kazakh women's casual costume is considered as an important element of ethnic culture, an indicator of cultural development, lifestyle and thoughts of society and an individual. The concept of the research is determined by understanding the worldview foundations expressed in a logically coherent typology and style of national costume, which can become the core of the spiritual modernization of modern society. Traditional culture, in particular national costume, has been the subject of many studies in the field of education, but this potential is still almost inexhaustible for the education and development of the young people thinking culture. As a unique example of the material and spiritual well-being of the Kazakh people, the costume harmoniously combines not only information and communication, aesthetic, ideological, semiotic, axiological, but also educational functions, while maintaining practical usefulness, utility, convenience, which have been polished for centuries. In addition, as the personification of the indissoluble ties of a person with the surrounding world, folk costume has invaluable opportunities to study the culture of other people, which is necessary for the formation of mutual tolerance.